Men’s Reproductive Health Services in the Northern Cape, - Mabote, Pheya Alinah (My University, 2011)
Very little research has been conducted on men’s reproductive health services in South Africa. The 1994 International Conference on Population and Development (ICPD) and the Fourth World Conference on Women in Beijing provided a foundation for expanding reproductive health services to include men. Many men and programme planners lack a clear understanding of what men’s reproductive health means. Services for men in South Africa are typically housed in settings where staff lack training in male sexuality and reproductive health. This research study was conducted in the Northern Cape. Three sets of data were used. The researcher undertook a situational analysis with key informants in order to understand the situation, services and needs for men’s sexual and reproductive health, identify barriers and obstacles to good quality reproductive health care and analysed existing plans and reports. Focus groups with men were conducted and key informants of the Department of Health were interviewed. The study has assessed progress made since the implementation of the National Health Plan of South Africa and has provided key future recommendations for the realization of ICPD adopted by South Africa in 1994. The findings of this research strongly emphasizes that all policies, programmes, information and services need to reflect the social realities of men and how this affects their health. The outcome of this research will be the development of a model that will serve as a framework for programme development and service delivery that will constitute basic reproductive health care for men. The study recommends that the Northern Cape Department of Health must design a reproductive health programme that integrates male health care including impotence, STIs, infertility and other conditions. Special advocacy vi strategies and messages should be developed to target men to raise awareness about their involvement in reproductive health This broader definition of male health will make it easier for men to walk into a health facility
MM - P&DM
Keywords: Reproductive health; Men's reproductive health; Health